Data and software preservation through containerisation in KM3NeT - Gál, Tamás (Proceedings of Science, 2019)
In this contribution we discuss of how we implemented procedures for maintaining and developing software and preserving data processing pipelines in KM3NeT using containerisation technologies and continuous integration.
CRIS-Team Scopus Importer:2021-04-20